Formation of germinal centres in the rat - Vonderheide, R (1988)
This thesis demonstrates a method based on the monoclonal antibody (mAb) HIS22 for distinguishing germinal centre B cells (GCC-B) of rat lymph nodes both in situ and in suspension. In two-colour flow cytometric studies, GCC-B were clearly identified as HIS22-negative, Ig-kappa-positive. For non-irradiated rats injected intravenously with B cells of the opposite kappa allotype, the relative distribution of donor B cells in GCs seven days after immunisation was calculated from FACS analysis using HIS22 and two anti-kappa alloantibodies. There were two general findings using this assay: (1) IgD-negative B cells found in the thoracic duct preferentially act as germinal centre precursor cells (GCPC), especially IgD-negative (memory) B cells isolated from primed donors, and (2) B cells primed to the specific, immunising antigen can immigrate into developing or well- developed germinal centres while unprimed B cells, one day or more after immunisation, cannot. A subset of T-helper cells, as indicated by their labelling with mAb ER3, make up the vast majority of T cells found in lymph node or splenic germinal centres; a necessary role for these cells in helping B cells form germinal centres was found. A subset of ER3-positive T-helper cells is 0X22-negative, implying that some ER3-positive cells are memory T cells. A previous suggestion that the Oxford mAb 157.6 recognises rat IgD was confirmed by immunoprecipitating the antigen from cell-surface iodinated proteins and comparing the pattern with that of mAb MARD-3 (anti-6 heavy chain). 157.6 labels 40%-60% of all IgD-positive cells (depending on the strain) and therefore identifies a serological heterogeneity of rat IgD.